Thinking social inequality between children: some feedback on qualitative research methodologies focused on children (Olhar de Professor, 2025)
This article aims to question social inequality between children who are considered as objects that are at once constructed and real, by taking a critical look at the qualitative research methodologies that focus on revealing inequality. On the one hand, by immediately associating children with the social characteristics of their parents, these methods involve an approach that is rooted in objectification and statistical totalization. On the other hand, “to make children speak” is not easy and puts more weight on testing children in social situations constituted by collective or individual interviews. In short, the pre-arranged character of testing applied to children and its inherently discriminatory character condemns research to ultimately find the social inequalities it has established from the outset. Doing research “with” children rather calls for other methodologies that take into account the expression of children and of the adults around them. It requires strong critical reflexivity and needs a hybrid design, based on distributed and situated children’s agency. The choice of tests to which these methodologies subject children, as well as the ways children are qualified, appear equally important in determining how inequalities between children are produced.
Keywords: Children; Qualitative methodology; Social inequalities; Agency